2018
DOI: 10.1021/acs.est.7b05172
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Modified Clay Controlling the Brown Tide Organism Aureococcus anophagefferens Revealed by Transcriptome Analysis

Abstract: The data and experiences in mitigating harmful algal blooms (HABs) by modified clay (MC) show that a bloom does not continue after the dispersal of the MC, even though the density of the residual cells in the water is still high, at 20-30% of the initial cell density. This interesting phenomenon indicates that in addition to flocculation, MC has an additional control mechanism. Here, transcriptome sequencing technology was used to study the molecular mechanism of MC in controlling HABs. In residual cells treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 68 publications
(121 reference statements)
1
14
0
Order By: Relevance
“…However, based on previous field experience, a removal efficiency of 70–80% is sufficient to control HABs, and the algal cells in the upper water do not regrow or contribute to a second bloom. Laboratory investigations on Aureococcus anophagefferens and Karenia mikimotoi showed that MC can disrupt the normal physiological processes in cells by inducing oxidative stress, inhibiting photosynthesis or causing other damage [ 29 , 30 , 31 ]. Moreover, water quality changes (such as the adsorption of nutrients and the effect of “mutual shading”) caused by MC were also explained by the inhibited growth of residual cells [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, based on previous field experience, a removal efficiency of 70–80% is sufficient to control HABs, and the algal cells in the upper water do not regrow or contribute to a second bloom. Laboratory investigations on Aureococcus anophagefferens and Karenia mikimotoi showed that MC can disrupt the normal physiological processes in cells by inducing oxidative stress, inhibiting photosynthesis or causing other damage [ 29 , 30 , 31 ]. Moreover, water quality changes (such as the adsorption of nutrients and the effect of “mutual shading”) caused by MC were also explained by the inhibited growth of residual cells [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al found that MC could effectively flocculate and settle P. globosa solitary cells and colonies [ 20 ], but the effects of MC on P. globosa cell growth and colony formation remained unclear. As previously mentioned, P. globosa tends to form colonies in resistance to environmental stresses [ 34 , 35 ], and MC presented indirect effects in controlling the growth of HABs [ 29 , 30 , 31 ]. Therefore, we assumed that the growth and colony formation of the remaining cells might be inhibited after MC treatment, which could potentially prevent the P. globosa blooms.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of ROS in cells can lead to the peroxidation of membrane lipids, which produces malondialdehyde. ROS may also give rise to DNA damage, blocking the transmission of genetic information, leading to upregulation of the cell cycle ( Zhu et al, 2018 ). The energy fixation and insufficient growth of algae (e.g., energy may be mainly used to buffer ROS) may severely inhibit DNA replication and repair ( Guo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…SMX blocks PSII electron transmission and further impedes the transmission of excitation energy from chlorophyll molecules (P680) to PSI ( Liu et al, 2011b ). The damaged electron transport chain may result in electron accumulation in the chloroplast, where oxygen molecules accept electrons to generate ROS that damages chloroplast in a continuous degradation cascade ( Zhu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The modified clay (MC) at a proper dose can flocculate with microscopic propagules and effectively remove microscopic 380 propagules from the water column (Li et al, 2020b). The physiological processes of Ulva cells could be disrupted by MC (Zhu et al, 2018). This method was frequently used to mitigate blooms in local areas (Li et al, 2017).…”
Section: Spatiotemporal Variation Of U Proliferamentioning
confidence: 99%